How women represent women political parties, gender, and representation in the state legislatures - Osborn, Tracy L., 1975- (New York ; Oxford : Oxford University Press, 2012)
This title argues that political parties fundamentally structure the ways in which women legislators represent women's interests. Using original election, sponsorship and roll call data across the US state chambers, Osborn shows how parties shape the policy alternatives women offer.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Women legislators -- United States -- States; Women -- Political activity -- United States -- States; Party affiliation -- United States -- States; Political parties -- United States -- States; Women -- Government policy -- United States -- States; Women -- Legal status, laws, etc. -- United States -- States